Neuroblastoma in a 17‐week fetus: A stimulus for investigation of tumors in a series of 2786 stillbirth and late miscarriages. (22nd October 2014) - McPherson, Elizabeth; Cold, Christopher; Johnson, Peter; Schema, Lynn; Zaleski, Christina
<x xml:space="preserve">Abstract</x> Although tumors are an occasional cause of neonatal death and have been reported in stillbirths, there are no studies specifically evaluating the frequency or types of tumors in stillborn infants. We observed metastatic neuroblastoma in a fetus miscarried at 17 weeks of gestational age. Fetal death was attributed to endocrine effects of the tumor causing fetal hypertension, arrhythmia, and/or placental dysfunction. This case, which is the earliest report of a pathologically confirmed neuroblastoma, prompted review of all tumors in the Wisconsin Stillbirth Service Program database. There were 10 lethal and two incidental tumors among the 2, 786 stillbirths and second trimester miscarriages in the database for an overall incidence of 1/232, which is about 50 times the incidence of clinically recognized tumors in liveborn infants. The most frequent tumors were teratoma and hemangioma that, while benign, caused death due to high output cardiac failure, hemorrhage into the tumor, or obstruction of vital organs. Only three tumors were malignant, and except for the index case, mechanisms of death were similar to those of the benign tumors. Except for the index case, all were found in the third trimester, suggesting that congenital tumors rarely become lethal until the third trimester. However, it is also possible that tumors may be missed in younger fetuses. The possibility of detecting an unsuspected tumor is yet another reason for autopsy in stillbirths and late miscarriages. © 2014 Wiley Periodicals, Inc.